The Mind and Language: The Mutual Degradation Psycholinguistic Investigation in Language Dissolution - Ibrahim Khudair, Amir (International Journal of Psychosocial Rehabilitation, 2020)
In this essay, the researcher draws the reciprocal relationship between the mind and language when both of them undergo certain degrees of declination. Therefore, he suggests that the starting point should be from the stuttering case concerning it as the most common language impairment that begins in childhood and normally vanishes in adulthood. Then, he shifts to Down’s syndrome and its linguistic consequences, setting off from its causes, symptoms, and the suggested mechanisms of lessening its effects on cognitive, psychological, and linguistic aspects.As the researcher talks about the deterioration of the mind and language, it is logical to investigate in the geriatric linguistic dissolution looking into the kinds of memory like short-term memory (STM) and long-term memory (LTM) and their role in the formation and deformation of language alike. Finally, autism is also checked due to its associated complexity of language disorder, where the affected individual suffers from isolation and alienation among his/her society. Isolation is like a solid wall preventing him/her from acquiring language because language is a result of a social interaction, and the lack of one entails the lack of the other.